PEMBINAAN SEMANGAT KERJA PEGAWAI PADA DINAS PENDIDIKAN KABUPATEN TANAH DATAR - Nola Octa Marlina (Jurnal Bahana Manajemen Pendidikan, 2013)
The study was grounded by optimizing and building morale officer at Tanah Datar education agencies. A survey is a data collection tool to model research method of rank correlation (Spearman method) submitted by Purwanto. Research result shows that building morale officer at Tanah Datar education agencies found that: (1) The overall average score on the granting of compensation to officers of the department of education leaders at KAB. Flat land is 3.6 6. This score is the Good category. (2) The overall turnover of the average score of all indicators is 3.74 lies in good category. (3) The overall average score on the placement of procurement officers in the right job by the leadership of Tanah Datar Department of Education has a 3.71 score and occupies a good category (4) In keseluruahn average score on the grant opportunity to develop themselves against the officer by leadership of the department of education is 3.59 Tanah Datar has good category. This means that the construction work of the spirit of education service officer at Tanah Datar. Kata Kunci: Semangat Kerja